The Abstract Book of the XIX Conference for Junior Scientists in Psychology - Nomeikaitė, Augustė; Rimkus, Evelina; Marcinkevičiūtė, Miglė (Vilnius University Proceedings, 2022)
Conference for Junior Scientists in Psychology is an annual event, organized by PhD students of Vilnius University, Institute of Psychology. The conference gives a platform for psychology students and junior researchers to present their scientific work and findings.
Keywords: Conference for Junior Scientists in Psychology; Psychology; Junior researchers